Determination of Ranitidine in Human Plasma by SPE and ESI-LC-MS/MS for Use in Bioequivalence Studies. (4th February 2013) - Bellorio, Karini B.; Alves, Maria Isabel R.; Antoniosi Filho, Nelson R.
Abstract : A method for determining ranitidine in human plasma by ESI-LC-MS/MS was validated, using propranolol as internal standard. The extraction method used was solid phase extraction (SPE). Chromatographic separation was performed in a Chromolith C18 (50 mm × 4.6 mm i.d.) analytical column, which provided good separation of ranitidine and propranolol peaks with an analysis time of 2.5 minutes. Extraction yields of 94.4% for ranitidine and 89.4% for the internal standard were obtained. The lower limit of quantification (LLOQ) was 3.00 ng/mL, and limit of detection (LOD) was 0.05 ng/mL, with linearity ranging from 3.00 to 500 ng/mL. The results, thus, showed that this method is suitable for application in bioequivalence studies of ranitidine in human plasma.